Future Classrooms: A Review of AI-Based Media Innovation and Gamification in Primary Schools - Gunawan Gunawan; Ni Made Yeni Suranti; Imran Imran; Fahmi Yahya (Indonesian Publication Center, 2025)
Digital transformation in primary education over the last five years (2020-2024) has drastically changed the landscape of learning media. This article aims to examine media innovations based on Artificial Intelligence (AI) and Gamification, as well as the role of immersive technologies such as Augmented Reality (AR) and Virtual Reality (VR) in Primary Schools. Through a literature review of selected studies, the analysis shows that AI implementation is effective in supporting deep learning in critical subjects such as Mathematics and language introduction. Meanwhile, gamification was found to play a significant role in increasing intrinsic motivation and ecological awareness, and is specifically capable of reducing students' academic anxiety in physical education and mathematics. The integration of AR and VR is proven to enrich sensory engagement and student creativity in language and arts learning. This review concludes that the synergy of AI-based media and gamification creates a